Environmental, Financial and Energy Implications of Renewable Energy Systems - Muktar, Anas; Yadaw, Praveen Kumar; Ahmad, Abubakar; Bello, Muhammad (Journal of Environmental and Energy Economics, 2024)
This paper explored various sustainability measures to evaluate renewable electricity generation systems, drawing from a comprehensive literature review. The metrics examined included energy payback time, greenhouse gas emissions, and electricity production costs. We found notable differences among the technologies in these areas. To enhance the assessment process, we introduced a novel figure of merit that combines greenhouse gas emissions, energy payback duration, and production costs into a single framework for ranking renewable energy sources. This approach not only facilitates clearer comparisons between technologies but also highlights the trade-offs inherent in sustainability evaluations. Our findings indicated that small hydro and wind power emerged as the most environmentally friendly electricity generation methods, reinforcing the need for a holistic evaluation in renewable energy research.